On the Boundary Conditions in Deformed Quantum Mechanics with Minimal Length Uncertainty - Pouria Pedram (Advances in High Energy Physics)
We find the coordinate space wave functions, maximal localization states, and quasiposition wave functions in a GUP framework that implies a minimal length uncertainty using a formally self-adjoint representation. We show how the boundary conditions in quasiposition space can be exactly determined from the boundary conditions in coordinate space.